2008
DOI: 10.1021/jp075464z
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Investigation on the Oxidation of Gallic Acid by Sulfate Radical Anions

Abstract: By monitoring the decay of SO4*- after flash photolysis of aqueous solutions of S2O82- at different pH values, the kinetics of the reaction of SO4*- radicals with gallic acid and the gallate ion was investigated. The bimolecular rate constants for the reactions of the sulfate radicals with gallic acid and the gallate ion were found to be (6.3 +/- 0.7) x 10(8) and (2.9 +/- 0.2) x 10(9) M(-1) s(-1), respectively. On the basis of the oxygen-independent second-order decay kinetics and on their absorption spectra, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 47 publications
(71 reference statements)
4
52
0
1
Order By: Relevance
“…4b; see the following text). Phenoxyl radicals of polyphenols are obtained by the reaction of one-electron oxidants, such as the azidyl [14], carbonate [19], and sulfate radicals [13,24], with these substrates.…”
Section: So4mentioning
confidence: 99%
See 1 more Smart Citation
“…4b; see the following text). Phenoxyl radicals of polyphenols are obtained by the reaction of one-electron oxidants, such as the azidyl [14], carbonate [19], and sulfate radicals [13,24], with these substrates.…”
Section: So4mentioning
confidence: 99%
“…Since the reactions of inorganic radicals with organic molecules important for biological processes are a relevant domain of research, the reaction of sulfate and phosphate radical anions with such molecules has been investigated in the literature [12][13][14]. In an attempt to make a contribution to the free radical chemistry of EC, ECG, and EGCG, in this study we investigated the reactions of sulfate and dihydrogen phosphate radicals with these flavonoids.…”
Section: Introductionmentioning
confidence: 99%
“…• , SO 4 •− and B 2 •− exhibits a maximum around 310 nm and a shoulder at ∼400 nm [12][13][14]. The spectrum of the phenoxyl radical formed from neutral MGA is similar to that of the GA.…”
Section: Introductionmentioning
confidence: 70%
“…Previously, Italian scientists had shown that compound 1 can be produced by in vitro radical oxidation of gallic acid. 18 They used sulfate radical anions to promote the reaction in laboratory conditions (Figure 3). It is probable that the compound 1 has been produced via oxidation reaction in a biological environment.…”
Section: Chemical Analysismentioning
confidence: 99%